Prejudice Toward Asian Americans in the Covid-19 Pandemic: The Effects of Social Media Use in the United States - Croucher, Stephen M.; Nguyen, Thao; Rahmani, Diyako (Frontiers in Communication, 2020)
The ongoing Covid-19 outbreak has brought increased incidents of racism, discrimination, and violence against “Asians,” particularly in the United States, with reports of hate crimes of over 100 per day. Since January 2020, many Asian Americans have reported suffering racial slurs, wrongful workplace termination, being spat on, physical violence, extreme physical distancing, etc., as media and government officials increasingly stigmatise and blame Asians for the spread of Covid-19. The links with social media are increasingly evident, as anti-Asian sentiment increases, with reports of anti-Asian sentiment spreading and Asian-Americans fighting hate via social media. Using integrated threat theory, this study explores the links between prejudice/hate toward Asians-Americans, in particular Chinese, and social media use. Three key results emerged from the study. First, the more a social media user believes their most used daily social media is fair, accurate, presents the facts, and is concerned about the public (social media believe), the more likely that user is to believe Chinese pose a realistic and symbolic threat to America. Second, men and women significantly differed on each type of prejudice, with men scoring higher on intergroup anxiety and women higher on symbolic and realistic threat. Third, respondents who do not use social media on a daily basis are less likely than those who use Facebook to perceive Chinese as a symbolic threat. Implications and recommendations for practitioners, health workers and government are proposed.